Statue of Jina Shantinatha - Temples of India Project Team (Jio Institute, 2024)
The tall, nude statue of Jina Shantinatha stands in meditation posture with a parasol above it, placed at the back of the temple's inner sanctum. The statue has a calm face with a slight smile and curly hair, although some parts like the hands, feet, and chest are slightly damaged. Two female attendant figures near its feet are also damaged, making it hard to identify them. The sculpture is carved out of sandstone.